Where do immigrants retire to? - Augustin de Coulon (IZA World of Labor, 2016)
As migration rates increase across the world, the choice of whether to retire in the host or home country is becoming a key decision for up to 15% of the world's population, and this proportion is growing rapidly. Large waves of immigrants who re-settled in the second half of the 20th century are now beginning to retire. Although immigrants' location choice at retirement is an area that has barely been studied, this decision has crucial implications for health care and social protection expenditures, both in host and origin countries.
Keywords: I15; I18; J61; J68; 330; immigration; retirement; country of residence